Physical activity and sitting time in adults after positive diagnosis for COVID-19: a cross-sectional study - Ramos, Ana Beatriz Minelli (2022)
This study aimed to: a) investigate the most common signs and symptoms reported by people infected by the COVID-19, b) compare total time and weekly level of physical activity of people between pre- and post-infection period, and c) examine the association between physical activity levels and signs and symptoms reported during the disease cycle. Twenty-two adult people (14 males and 8 females, mean age 37.9 ± 16.8 years) living in Ribeirão Preto, Brazil participated in this study. Participants received a positive diagnosis for COVID-19 by PCR. Physical activity and sitting time was assessed using the International Physical Activity Questionnaire. Variables such as body mass index and the clinical condition of the disease (signs and symptoms) were collected. The most frequent signs and symptoms reported by active and inactive individuals, respectively, were loss of taste (77.8% and 25%), headache (66.7% and 25%), coughing (66.7% and 25%), difficulty breathing (61.1% and 25%), and sore throat (61.1% and 75%). A 120-minute reduction (p = 0.010) in the total time of weekly physical activity and a 155 minute reduction (p = 0.003) of weekly moderate physical activity was observed in the pre- and post-diagnostic COVID-19 infection comparison. There was further an association between difficulty breathing and being physically inactive (odds ratio = 0.222; 95%CI: 0.094 – 0.527). Our findings suggest that COVID-19 had a negative impact on physical activity and that being physically active may reduce the likelihood of presenting with difficulty breathing if infected with the SARS-CoV-2 and associated disease COVID-19.